Effect of pediatric drugs on solubility of restorative materials used in primary teeth - U., Mridhul M.; Ayilliath, Ambili; Ephraim, Rena; Chandrashekhar, Sharath (International Journal of Contemporary Pediatrics, 2021)
Background: Pleasant tasting syrups have a long history of use in pediatric practice to aid compliance with medication. Pharmaceutical firms sweeten liquid drug preparations with sucrose to increase the palatability which causes dental caries and erosion in children. In pediatric population, the commonly used esthetic restorative materials are glass ionomers, compomers or composites. Hence solubility of dental restorative materials are of considerable clinical importance and cannot be overlooked. Aims and objectives of current study were to evaluate the effect of commonly used pediatric drugs on the surface solubility of pediatric restorative materials. Methods: The study was conducted on 40 disc shaped specimens of GIC and composite immersed in artificial saliva and pediatric drugs, at 370C for 7 days to determine the solubility in pediatric drug formulations. The solubility of the specimens was calculated by a given formula by comparing the initial and final masses of the specimens. Results: In both GIC and Composite groups higher solubility was seen with paracetamol drug formulations. The mean solubility value of GIC was 0.14±0.02 and that of composite was 0.07±0.035, in paracetamol drug formulations. Conclusions: From the above experimental study it can be concluded that the solubility of restorative materials were comparatively higher in pediatric liquid medications with low pH. Among the drugs paracetamol showed increased erosive effects leading to solubility.